2018
DOI: 10.1186/s13033-018-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy of school nurses in the United Arab Emirates

Abstract: BackgroundTo support promotion, prevention and early intervention for mental illness school nurses need to be mental health literate.MethodsThree hundred and thirty-nine school nurses employed in government and private schools from three Emirates in the UAE were surveyed. A culturally adapted Mental Health Literacy questionnaire comprising three vignettes of fictional characters meeting diagnostic criteria for the target conditions along with the Kessler Psychological Distress Scale (K10) was administered to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(89 citation statements)
references
References 33 publications
5
81
1
2
Order By: Relevance
“…The given literacy in health professionals can also be an important factor affecting nurses' decision-making and functioning in health systems to improve public health. [25] Because nurses are among the groups employed in the domain of healthcare and also engaged in repeated relationships with healthcare issues in hospitals, they need to have an optimal level of health literacy; thus, the results obtained in the present study confirmed this issue. According to the findings of this study, quality of life in nurses was estimated at moderate levels.…”
Section: Discussionsupporting
confidence: 70%
“…The given literacy in health professionals can also be an important factor affecting nurses' decision-making and functioning in health systems to improve public health. [25] Because nurses are among the groups employed in the domain of healthcare and also engaged in repeated relationships with healthcare issues in hospitals, they need to have an optimal level of health literacy; thus, the results obtained in the present study confirmed this issue. According to the findings of this study, quality of life in nurses was estimated at moderate levels.…”
Section: Discussionsupporting
confidence: 70%
“…For example, a previous study found teachers had limited sensitivity to variations in students' levels of anxiety symptoms, and often struggled to identify students that required targeted interventions or additional classroom support [26]. Research conducted in the United Arab Emirates (UAE) reported that correct identification of mental health problems and accurate identification of appropriate evidence-based interventions for affected children was limited among healthcare professionals [27,28]. This was attributed to low levels of mental health literacy among respondents, combined with religious and cultural factors that potentially affected their interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the UAE has a large percentage of young people with developmental needs that may predispose them to anxiety in adulthood, especially those with chronic conditions [27]. The UAE also has specific environmental and cultural risk factors that contribute to mental health problems, particularly among young people [28,30]. These risk factors include large family units and consanguineous marriages, which are common in the UAE and the wider Arab world [31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study found teachers had limited sensitivity to variations in students' levels of anxiety symptoms, and often struggled to identify students that required targeted interventions or additional classroom support [26]. Research conducted in the United Arab Emirates (UAE) reported that correct identi cation of mental health problems and accurate identi cation of appropriate evidence-based interventions for affected children was limited among healthcare professionals [27,28]. This was attributed to low levels of mental health literacy among respondents, combined with religious and cultural factors that potentially affected their interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the UAE has a large percentage of young people with developmental needs that may predispose them to anxiety in adulthood, especially those with chronic conditions [27]. The UAE also has speci c environmental and cultural risk factors that contribute to mental health problems, particularly among young people [28,30].…”
Section: Introductionmentioning
confidence: 99%